Regulatory affairs for biomaterials and medical devices - Amato, Stephen F.; Ezzell, Robert M., Jr (Woodhead Publishing series in biomaterials, 2015)
All biomaterials and medical devices are subject to a long list of regulatory practises and policies which must be adhered to in order to receive clearance. This book provides readers with information on the systems in place in the USA and the rest of the world. Chapters focus on a series of procedures and policies including topics such as commercialization, clinical development, general good practise manufacturing and post market surveillance. Addresses global regulations and regulatory issues surrounding biomaterials and medical devicesEspecially useful for smaller companies who may not emplo.